Applications of Fiber Optic Sensor for Monitoring and Early Warning of Soil Shift on IoT based System - Herlin, Helmi Septaria; Harmadi, -; Febrielviyanti, -; Muldarisnur, - (JOIV : International Journal on Informatics Visualization, 2020)
A fiber optic sensor system has been designed to monitor ground shift using a multimode FD-620-10 step index fiber optic cable equipped with an IoT-based data transmission system. The sensor system consists of a light source in the form of a diode laser, a fiber optic cable light wave guide, and an OPT101 photodetector. Data processing is done using the Arduino Uno R3 microcontroller and data transmission to the server using the Arduino Ethernet Shield. Localhost is a webserver that displays measurement data and sends e-mail early warning notification of ground shift hazards. Optical fiber is used to measure the value of ground displacement by utilizing changes in output voltage. The change in output voltage occurs due to variations in the change in the diameter of the optical fiber arch. The results of sensor testing obtained an average measurement error of 1.53%.